(untitled) (Razão e Fé, 2020)
This work aims to explain the educational thought process in Brazil, focusing on some philosophical currents, in particular, the Enlightenment and Positivism. It will take into account the historical context for such an approach, from European philosophical thought (introduced to our country by the Jesuit method of evangelization) to the influence of the technicist method left by the positivist legacy (whose ideal was order and progress). From a global perspective, we will seek to demonstrate, through a theoretical reference research, the educational challenges in the 21st century, as well as to suggest teaching proposals for overcoming the incrustations left by the positivist model. The critical character of contemporary methodological views on the traditional form of education are present in this work, in order to seek a way to rethink the relationships between the educator and his students. Traditional teaching, by adopting a monological stance of teaching, can no longer achieve knowledge that inspires, in the student, the criticality about reality; it only gives it the ability to reproduce pre-established propositions. As a proposal, the article points out models of education that link pedagogy to the philosophy of education, establishing a bond capable of building in students and teachers a mutual relationship of knowledge, learning and teaching.